Mass production of ultra-pure NaI powder for COSINE-200 - Shin, KeonAh; Choe, JunSeok; Gileva, Olga; Iltis, Alain; Kim, Yena; Kim, Yeongduk; Lee, Cheolho; Lee, Eunkyung; Lee, HyunSu; Lee, Moo Hyun (Frontiers in Physics, 2023)
COSINE-200 is the next phase experiment of the ongoing COSINE-100 that aims to unambiguously verify the annual modulation signals observed by the DAMA experiment and to reach the world competitive sensitivity on the low-mass dark matter search. To achieve the physics goal of the COSINE-200, the successful production of the low-background NaI(Tl) detectors is crucial and it must begin from the mass production of the ultra-low background NaI powder. A clean facility for mass-producing the pure-NaI powder has been constructed at the Center for Underground Physics (CUP) in Korea. Two years of operation determined efficient parameters of the mass purification and provided a total of 480 kg of the ultra-pure NaI powder in hand. The potassium concentration in the produced powders varied from 5.4 to 11 ppb, and the maximum production capacity of 35 kg per 2 weeks was achieved. Here, we report our operational practice with the mass purification of the NaI powder, which includes raw powder purification, recycling of the mother solution, and recovery of NaI from the residual melt after crystal growth.